Drug-coated balloon for treatment of de-novo coronary artery lesions in patients with high bleeding risk (DEBUT): a single-blind, randomised, non-inferiority trial. Issue 10194 (20th July 2019) - Rissanen, Tuomas T; Uskela, Sanna; Eränen, Jaakko; Mäntylä, Pirjo; Olli, Annika; Romppanen, Hannu; Siljander, Antti; Pietilä, Mikko; Minkkinen, Mikko J; Tervo, Jerry; Kärkkäinen, Jussi M; ,
Summary: Background: The optimal technique of percutaneous coronary intervention in patients at high bleeding risk is not known. The hypothesis of the DEBUT trial was that percutaneous coronary intervention with drug-coated balloons is non-inferior to percutaneous coronary intervention with bare-metal stents for this population. Methods: The DEBUT trial is a randomised, single-blind non-inferiority trial done at five sites in Finland. Patients were eligible if they had an ischaemic de-novo lesion in a coronary artery or bypass graft that could be treated with drug-coated balloons, at least one risk factor for bleeding, and a reference vessel diameter of 2·5–4·0 mm. Those with myocardial infarction with ST-elevation, bifurcation lesions needing a two-stent technique, in-stent restenosis, and flow-limiting dissection or substantial recoil (>30%) of the target lesion after predilation were excluded. After successful predilation of the target lesion, patients were randomly assigned (1:1), by use of a computer-generated random sequence, to percutaneous coronary intervention with a balloon coated with paclitaxel and iopromide or a bare-metal stent. The primary outcome was major adverse cardiac events at 9 months. Non-inferiority was shown if the absolute risk difference was no more than 3%. All prespecified analyses were done in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, number NCT01781546 . Findings: Between May 22, 2013, and Jan 16, 2017, 220 patients were recruited for the study and 208 patients were assigned to percutaneous coronary intervention with drug-coated balloon (n=102) or bare metal stent (n=106). At 9 months, major adverse cardiac events had occurred in one patient (1%) in the drug-coated balloon group and in 15 patients (14%) in the bare-metal stent group (absolute risk difference −13·2 percentage points [95% CI −6·2 to −21·1], risk ratio 0·07 [95% CI 0·01 to 0·52]; p<0·00001 for non-inferiority and p=0·00034 for superiority). Two definitive stent thrombosis events occurred in the bare metal stent group but no acute vessel closures in the drug-coated balloon group. Interpretations: Percutaneous coronary intervention with drug-coated balloon was superior to bare-metal stents in patients at bleeding risk. The drug-coated balloon-only coronary intervention is a novel strategy to treat this difficult patient population. Comparison of this approach to the new generation drug-eluting stents is warranted in the future. Funding: B Braun Medical AG, AstraZeneca, and Competitive State Research Funding of the Kuopio University Hospital Catchment Area.